2021
DOI: 10.31548/agr2021.04.091
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen mode of black earth normal in tekhnology "No-till"

Abstract: Studies of the influence of different technologies of ordinary chernozem cultivation on the reserves of productive moisture for growing corn for grain and winter wheat in the steppe zone of Ukraine The parameters of productive moisture at the technology of growing field crops with "zero tillage" of the soil ("No-till") relative to the shelf plowing are determined. Inserted. That the system "No-till" contributes to a significant reduction in moisture loss due to unproductive evaporation at a high rate of absorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 6 publications
0
0
0
Order By: Relevance
“…It should also be noted that both in the top (0-10 cm) and in the 10-20 and 20-30 cm horizons, the soil texture density indicators had critical limits and significantly exceeded the optimal parameters for soybeans. Similar results were obtained by R.A. Vozhehova et al (2021), who found that the lowest level of soil density (1.23 g/cm 3 ) was formed under chisel tillage to a depth of 28-30 cm of soil, which is 1.6% lower than the control (ploughing at 28-30 cm), and the highest (1.29 g/cm 3 ) was obtained under the No-till system, which is 3.2% higher than the control. However, S.R.…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…It should also be noted that both in the top (0-10 cm) and in the 10-20 and 20-30 cm horizons, the soil texture density indicators had critical limits and significantly exceeded the optimal parameters for soybeans. Similar results were obtained by R.A. Vozhehova et al (2021), who found that the lowest level of soil density (1.23 g/cm 3 ) was formed under chisel tillage to a depth of 28-30 cm of soil, which is 1.6% lower than the control (ploughing at 28-30 cm), and the highest (1.29 g/cm 3 ) was obtained under the No-till system, which is 3.2% higher than the control. However, S.R.…”
Section: Resultssupporting
confidence: 89%
“…It is known that the most favourable conditions for growing soybeans are created when the soil density is in the range of 1.1-1.3 g/cm 3 . M.T.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations